ANALISIS PELAKSANAAN PROGRAM SUMBER DAYA MANUSIA KESEHATAN (SDMK) DI DINAS KESEHATAN PROVINSI RIAU - Yan Fitri, Eka; Jepisah , Doni; Anusirwan (LPPM Universitas Awal Bros, 2025)
Health Human Resources (HHR) management is a fundamental component of health system delivery, supporting promotive, preventive, curative, and rehabilitative services. In Indonesia, strengthening HHR is a key element of the ongoing health system transformation, including in Riau Province, which faces geographical challenges, unequal distribution of health personnel, and varying managerial capacities across districts. One of the most prominent issues is the inconsistency and lack of updated HHR data between central and regional levels due to irregular data updates in the Health Human Resources Information System (SISDMK). This study aims to analyze the implementation of the HHR Program at the Riau Provincial Health Office using a qualitative case study approach involving observations, in-depth interviews, and document review. Data were analyzed using the Urgency–Seriousness–Growth (USG) method to prioritize problems and the Fishbone model to identify root causes. The findings indicate that outdated HHR data is the top priority issue, influenced by factors related to manpower, methods, technology, materials, management, and funding. Strategic solutions include mandatory monthly data updates, strengthened operator coordination, development of standard operating procedures, provision of technical guidelines, and regular provincial-level mentoring.